Synthesis of nanocrystalline tetragonal zirconia by a polymeric organometallic method - Quinelato, Antonio L.; Longo, Elson; Leite, Edson R.; Varela, José A. [UNESP] (My University, 1999)
A polymeric precursor method based on the Pechini process was successfully used to synthesize zirconia-12 mol% ceria ceramic powders. The influence of the main process variables (citric acid-ethylene glycol ratio, citric acid - total oxides ratio and calcination temperature) on phase formation and powder morphology (surface area and crystallite size) were investigated. The thermal decomposition behavior of the precursor is presented. X-ray diffraction (XRD) patterns of powders revealed a crystalline tetragonal zirconia single-phase, with crystallite diameter ranging from 6 to 15 nm. The BET surface areas were relatively high, reaching 95 m2 g-1. Nitrogen adsorption/desorption on the powders suggested that nonaggregated powders could be attained, depending on the synthesis conditions. Copyright © 1999 John Wiley & Sons, Ltd.
Keywords: Ceramic; Pechini process; X-ray diffraction; Zirconia